1999
DOI: 10.1038/sj.onc.1202739
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression assay of chromosome arm 8p genes identifies Frizzled-related (FRP1/FRZB) and Fibroblast Growth Factor Receptor 1 (FGFR1) as candidate breast cancer genes

Abstract: Deletions and ampli®cations are frequent alterations of the short arm of chromosome 8 associated with various types of cancers, including breast cancers. This indicates the likely presence of tumor suppressor genes and oncogenes. In the present study, we have used the expressed sequence tag (EST) map of 8p11-21 to assemble a set of available cDNAs representing genes from this region. DNA arrays were prepared for expression analysis and search for genes potentially involved in breast cancer. Underexpresion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 45 publications
8
104
0
1
Order By: Relevance
“…On the basis of their expression array analysis of chromosome 8p11-21 genes, Ugolini et al (1999) reported that expression of SFRP1 mRNA is frequently diminished or lost in breast carcinomas, and they also found that loss of SFRP1 occurs in more than 80% of invasive breast carcinomas, although not in the medullary type (Ugolini et al, 2001). Using immunohistochemical analysis, Klopocki et al (2004) found that expression of SFRP1 protein was absent in 46% of invasive breast tumours and in 43% of carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their expression array analysis of chromosome 8p11-21 genes, Ugolini et al (1999) reported that expression of SFRP1 mRNA is frequently diminished or lost in breast carcinomas, and they also found that loss of SFRP1 occurs in more than 80% of invasive breast carcinomas, although not in the medullary type (Ugolini et al, 2001). Using immunohistochemical analysis, Klopocki et al (2004) found that expression of SFRP1 protein was absent in 46% of invasive breast tumours and in 43% of carcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2000) also showed that nuclear and/or cytoplasmic staining of b-catenin correlated with elevated cyclin D1, which is one of the known targets of b-catenin/TCF transcription. However, mutation of APC, CTNNB1 or AXIN is rare in breast cancer, and thus the mechanism of Wnt signal activation in this disease is not fully understood.On the basis of their expression array analysis of chromosome 8p11-21 genes, Ugolini et al (1999) reported that expression of SFRP1 mRNA is frequently diminished or lost in breast carcinomas, and they also found that loss of SFRP1 occurs in more than 80% of invasive breast carcinomas, although not in the medullary type (Ugolini et al, 2001). Using immunohistochemical analysis, Klopocki et al (2004) found that expression of SFRP1 protein was absent in 46% of invasive breast tumours and in 43% of carcinoma in situ.…”
mentioning
confidence: 99%
“…The array CGH also suggests the region proximal to this deletion and before the centromere may also be amplified, but this was not investigated further. This region may include the ANK1 and PLAT genes which can be amplified separately (Ugolini et al, 1999).…”
Section: Zr-75-1mentioning
confidence: 99%
“…This amplicon was present in 24% of primary breast tumours and found to correlate with poor survival (Garcia et al, 2005;Prentice et al, 2005). The long-suspected amplification target, FGFR1, was excluded from the current consensus amplicon and detected as amplified in fewer, 10-15%, of cases (Theillet et al, 1993;Ugolini et al, 1999;Prentice et al, 2005). Amplification of proximal 8p is also seen in other carcinomas (Veltman et al, 2003;Nakao et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation